As interfaces das relações de poder nas decisões do Conselho Municipal dos Direitos da Criança e do Adolescente de Sorocaba (SP) sobre o Fundo Municipal dos Direitos da Criança e do Adolescente - 2006 a 2008 - Carlos, Carla Jacques (2009)
The object of this dissertation is the expressions of power relations at the decisions of the Child and Adolescent Rights City Council of Sorocaba about the Child and Adolescent Rights City Fund, from 2006 to 2008. The objective is to know and analyze aspects of power relations that cross the CCCAR of Sorocaba in its connections with the local political culture. The formulate hypothesis is that the decisions of CCCAR of Sorocaba about the CARCF are predominantly crossed by power relations that contribute for the clientelism maintenance at this sphere. It's a qualitative research and had as methodological procedures, the documentary research, the bibliographic survey, the researcher's participant observation and the field research. The empirical research was fulfilled through the Oral History methodology since it confers visibility and centrality to the political subjects, enlightens the meanings in its narratives making the experiences elucidated in the collecting process of the testimonies reliable. Testimonies from 8 subjects were collected, three of them watched for a longer period the story of Council. However, all of them show a role of emphasis at the city political scenario, bound to the Child and Adolescent Rights issues. The bibliographic survey had as references the following concepts: power relations, political culture, the democracy and the rights, under an interdisciplinary foundation, having as line of thought a critical historical-political-cultural analysis, and the documentary analysis involved the data research about the social reality of the child and adolescent in Sorocaba and as regards the Council in lines, objective to clarify not exclusively the theoretical corps about the Rights Council, but also to contribute for the political practice of this democratic institution